Assessment of Counselling Services Available to Prison Inmates in South-East, Nigeria - Ngozi Nwadik, Angela; Ogbonnaya Okor, Nwaeze; C. Nwefuru, Bartholomew (International Journal of Psychosocial Rehabilitation, 2021)
The study investigated availability of counselling services in South East, Nigeria prisons. Based on the purpose of the study, one research question was raised and a hypothesis postulated that guided the study. It employed descriptive Survey design. Population of the study was 9,241 prison inmates. Multi-stage sampling procedure was used to select a sample of 924 subjects comprising 116 convicted inmates and 808 non-convicted prison inmates. The instrument for data collection was Questionnaire for Counselling Services in Prison (QCSP). The face and content validities of the instrument was assured. In determining the reliability of the instrument, Cronbach Alpha test was used, reliability co-efficient of 0.81 was obtained. The research question raised was answered using descriptive statistic (Frequency and percentage scores). The major findings showed that there are counselling services for prison inmates in South-East Nigeria. There was no significant difference between the responses of convicted and non-convicted prison inmates on the counselling services available to prison inmates